THE MEDIATING ROLE OF BUSINESS PERFORMANCE IN THE RELATIONSHIP BETWEEN ENTREPRENEURIAL COMPETENCY, BUSINESS STABILITY AND BUSINESS FINANCING - Widayati, Enny; Aziz, Zuraimi Abdul; Mukhtar, Dzulkifli; Yunaz, Haswan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Previous research has shown inconsistent results regarding the direct influence of entrepreneurial competency and business stability on SME performance. This study offers new insights by identifying business financing as a mediating variable that strengthens the impact of both factors on business performance. The results indicate that entrepreneurial competency and business stability may have limited direct effects, but their influence becomes significant when SMEs have adequate access to and control over financial resources. Financial capacity thus serves as a strategic enabler, allowing internal strengths to generate improved business outcomes. The study involved 93 SME entrepreneurs, with data collected using a structured questionnaire that measured entrepreneurial competency, business stability, business financing, and business performance. The data were analysed using Structural Equation Modelling with the Partial Least Squares (SEM-PLS) approach. Findings confirm the mediating role of business financing and highlight its importance in supporting SME growth and sustainability.